The Westing game - Raskin, Ellen (New York, N.Y., U.S.A. : Puffin Books, 1992)
The mysterious death of an eccentric millionaire brings together an unlikely assortment of heirs who must uncover the circumstances of his death before they can claim their inheritance.
750
Keywords: Newbery Medal; Mystery and detective stories